SILAC‐based quantitative proteomic analysis of secretome of Marc‐145 cells infected with porcine reproductive and respiratory syndrome virus. Issue 20 (6th September 2016) - Zhao, Fuwei; Fang, Liurong; Wang, Dang; Song, Tao; Wang, Ting; Xin, Yinghao; Chen, Huanchun; Xiao, Shaobo
Abstract : Porcine reproductive and respiratory syndrome virus (PRRSV) is the causative agent of PRRS, which causes severe reproductive failure in sows, respiratory disease in young and growing pigs, and enormous economic losses to the global swine industry. In this study, SILAC combined with MS/MS was used to quantitatively identify the secretory proteins differentially expressed in PRRSV‐infected Marc‐145 cells compared with mock‐infected controls. In total, we identified 204 secretory proteins showing significant differences in infected cells (163 upregulated, 41 downregulated). Intensive bioinformatic analysis of secretome data revealed that PRRSV infection strongly activated nonclassical protein secretion, especially vesicle‐mediated release of exosomal proteins, including different danger‐associated molecular pattern molecules and the majority of secreted proteins involved in protein binding and transport, regulation of response to stimulus, metabolic processes, and immune responses. According to the functional proteins analysis, we speculate that proteins functioning in binding, transport, and the immune response are exploited by PRRSV to facilitate virus replication and immune evasion. Our study for the first time analyzes the secretory protein profile of PRRSV‐infected Marc‐145 cells and provides valuable insight into the host response to PRRSV infection.